2001
DOI: 10.1177/136578280103300417
|View full text |Cite
|
Sign up to set email alerts
|

A simplified daylighting design tool for high-density urban residential buildings

Abstract: The paper describes a simple design tool for architects to estimate daylight performance of high-rise residential buildings in high-density urban sites during the early design stage. The tool is based on a modified version of the original split flux formulae. The tool resolves the formulae to a set of tables relating vertical obstruction angles with horizontal obstruction angles. Given the geometrical properties and the required daylight performances, an architect could work out, at the early design and planni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 3 publications
0
40
0
Order By: Relevance
“…
Figure 9.Example of high-density residential block plan in Hong Kong. Source: Adapted from Ng 41 (Fig. 4, p. 264)
…”
Section: Visualising Lightmentioning
confidence: 99%
See 1 more Smart Citation
“…
Figure 9.Example of high-density residential block plan in Hong Kong. Source: Adapted from Ng 41 (Fig. 4, p. 264)
…”
Section: Visualising Lightmentioning
confidence: 99%
“…70 Ng addressed the problem of mega-cities and high density living rapidly becoming the norm in Asian cities. For such high-density residential sites (Figure 9) he proposed a simple design method 71 for urban designers to use at the preliminary design stage which assessed average daylight factor in terms of vertical and horizontal obstruction and window glazing area. This was to allow the provision of better daylit interiors in these high-density residential blocks.…”
Section: Visualising Lightmentioning
confidence: 99%
“…External light reflected from nearby buildings and sunlit streets were further modeled to estimate mean daylight illuminance in rooms facing sunlit streets [27]. Further research was carried out to model indoor illumination under high density urban residential buildings where windows face varied obstructions [28,29]. Perez et al [30] developed an 'All-Weather' model for Berkeley with five variable coefficients depending upon sky clearance, sky brightness and solar altitude based upon the original model by Perez [31].…”
Section: Methods For Estimating Natural Illumination Inside Buildingsmentioning
confidence: 99%
“…The whole sky hemisphere has been divided into 145 elements [111] and then relative luminance distributions have been calculated as suggested by Li et al [43]. Source: [28]. Sky-diffuse component is divided into 145 angular zones and then summed up as follows: E k;ij ¼ X 145 l¼1 lv l;k;ij DS l cos r l ¼ X 145 l¼1 lv k DS l cosð/ l À / surf Þ ð A37Þ Therefore for each sky condition E k;ij gives luminance of the sky diffuse component for a particular element.…”
Section: Inferences and Conclusionmentioning
confidence: 99%
“…Despite of its importance, researches dedicated to daylight assessment in dense urban spaces, are relatively recent. Internationally, examples of this kind of study can be found in the publications by Tsangrassoulis et al (1999) for estimating illuminances in urban canyons, by Ng (2001) for daylight design in high-density urban residential buildings using a metric for overcast sky, and by Reinhart and LoVerso (2010) about a design sequence for diffuse daylight based on design "rules of thumb".…”
Section: Introductionmentioning
confidence: 99%